Secondary Bacterial Infections During Pulmonary Viral Disease: Phage Therapeutics as Alternatives to Antibiotics? - Manohar, Prasanth; Loh, Belinda; Athira, Sudarsanan; Nachimuthu, Ramesh; Hua, Xiaoting; Welburn, Susan C.; Leptihn, Sebastian (Frontiers in Microbiology, 2020)
Secondary bacterial infections manifest during or after a viral infection(s) and can lead to negative outcomes and sometimes fatal clinical complications. Research and development of clinical interventions is largely focused on the primary pathogen, with research on any secondary infection(s) being neglected. Here we highlight the impact of secondary bacterial infections and in particular those caused by antibiotic-resistant strains, on disease outcomes. We describe possible non-antibiotic treatment options, when small molecule drugs have no effect on the bacterial pathogen and explore the potential of phage therapy and phage-derived therapeutic proteins and strategies in treating secondary bacterial infections, including their application in combination with chemical antibiotics.